INTEREST POLICY OF COMMERCIAL BANKS IN FOREIGN CURRENCY (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article delves into the interest policies adopted by commercial banks in handling foreign currency. With globalization and increased cross-border transactions, understanding how banks manage interest rates in foreign currencies becomes crucial. The study aims to provide insights into the factors influencing these policies, their impact on monetary stability, and the risk management strategies employed by banks.